Ron Machin - Patti Machin:::Creator::::::::::::
Ron Machin, sculptor of Steinbeck bust in number 1-245. The finished bust was donated by the author and is on display in the Martha Heasley Cox Center for Steinbeck Studies in 2015. Digital copy only. No hard copy.